Cleavings: Critical Losses in the Politics of Gain - Davidson, Michael (Disability Studies Quarterly, 2016)
Many of Emily Dickinson's best known poems deal with the loss of sight, based on her own experiences with temporary blindness in the mid 1860s, but they are less about the absence of sight than about how she experiences the limits of consciousness: "I could not see to see." She probed the loss of sensation for what it could teach her about what is most familiar—and thus invisible. Using poems by Emily Dickinson and recent work in cultural and queer theory, this essay explores the fine line between "gain" and "loss" in disability studies. Using the author's experience of sudden hearing loss, "Cleavings" argues that recent claims for "deaf gain" have vaunted possibilities of cultural inclusiveness to the exclusion of affective realms of frustration, loss, and failure that are seldom acknowledged experiences of deaf and hard-of-hearing persons. While endorsing the general thrust of deaf gain and its implications for the larger context of disability, "Cleavings" argues for a more critical understanding of loss in the politics of gain.